Le suivi à la trace : les contraintes des sportifs appartenant aux groupes cibles - Lapouble, J.-C. (Movement & Sport Sciences - Science & Motricité, 2016)
The whereabout system created by the World Anti-Doping Code is not without raising questions about the invasion of privacy it entails. The movement of certain strictly personal information is not safe in some countries. In addition, the current law remedies appear limited and/or inadequate.